2005
DOI: 10.1086/426827
|View full text |Cite
|
Sign up to set email alerts
|

How Soon after Infection with HIV Does the Risk of Tuberculosis Start to Increase? A Retrospective Cohort Study in South African Gold Miners

Abstract: The increase in the risk of TB so soon after infection with HIV was unexpected. Current predictive models of TB incidence underestimate the effect of HIV infection in areas where TB is endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
269
1
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(286 citation statements)
references
References 41 publications
6
269
1
10
Order By: Relevance
“…Renewed global interest led to advances in recognising TB/HIV co-infection and understanding the mechanisms promoting susceptibility of HIV-infected people in developing TB disease as part of a multifactorial process [26-30]. Diagnosis of HIV/TB co-infection in children is still challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed global interest led to advances in recognising TB/HIV co-infection and understanding the mechanisms promoting susceptibility of HIV-infected people in developing TB disease as part of a multifactorial process [26-30]. Diagnosis of HIV/TB co-infection in children is still challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of active TB increases with depletion of CD4 T-cells, but studies have also shown that HIV positive individuals in high TB incidence regions have an increased risk of developing active TB in the first year after HIV seroconversion, i.e. with high CD4 T-cell counts [26]. In addition, HIV positive individuals on ART with high CD4 T-cell counts continue to have an increased risk of developing TB compared with uninfected controls.…”
Section: Impact Of Hiv On Pathogenesis Of Tbmentioning
confidence: 99%
“…Unlike other opportunistic infections, the risk of developing active TB is greatly increased in persons even before significant depletion of CD4 1 T cells in peripheral blood (2). In high transmission regions, most TB cases in HIV-individuals result from recent Mycobacterium tuberculosis (Mtb) infection indicating that in these individuals the lung is more permissive for the establishment or progression of primary infections (3).…”
mentioning
confidence: 99%
“…The mortality rate has reached 20% in that region, compared to 5% in countries with good tuberculosis control programs [3]. Moreover, there is an annual increase of 10% in the number of TB cases in these African countries, mainly among individuals between 15 and 49 years old [5].…”
mentioning
confidence: 99%
“…The risk of developing active TB in HIV patients increases from 5 to 15% annually, due to the latent infection being reactivated; this depends on the degree of immunocompromise [12,14,15]. A study conducted among gold miners in South Africa showed that the risk of TB doubles within one year of HIV infection, but only increases slightly during the following years [5]. It has been noted that pulmonary TB occurs relatively early in the spectrum of HIV related infections and often before other AIDS-defining conditions.…”
mentioning
confidence: 99%